Inflammatory cells contribute to the generation of an angiogenic phenotype in pancreatic ductal adenocarcinoma. Issue 6 (27th May 2004) - Esposito, I; Menicagli, M; Funel, N; Bergmann, F; Boggi, U; Mosca, F; Bevilacqua, G; Campani, D
Abstract : Background: Inflammatory cells contribute to the growth and spread of human malignancies by producing molecules that enhance tumour invasiveness. Aims: To characterise the inflammatory infiltrate in pancreatic ductal adenocarcinoma and to analyse its contribution to angiogenesis and its prognostic relevance. Methods: Immunohistochemistry was used to identify inflammatory cells and evaluate the expression of proangiogenic and prolymphangiogenic molecules (vascular endothelial growth factor A (VEGF-A), VEGF-C, and basic fibroblast growth factor (bFGF)) by inflammatory and cancer cells in 137 pancreatic cancers. Intratumorous microvessel density (IMD) was assessed using CD34 as an endothelial cell marker. Results: There were significantly more mast cells and macrophages in pancreatic cancers than in normal pancreas and the number of mast cells directly correlated with the presence of lymph node metastases. However, there was no relation between numbers of infiltrating inflammatory cells and the presence of chronic pancreatitis (CP)-like changes in the parenchyma surrounding the tumour. Double immunostaining revealed that both pancreatic mast cells and macrophages express VEGF-A, VEGF-C, and bFGF. These factors were also expressed in the tumour cells in many cases. The numbers of VEGF-A expressing tumour cells and bFGF expressing tumour and inflammatory cells significantly correlated with IMD. Moreover, tumours with higher IMD had higher numbers of infiltrating mast cells and macrophages. Conclusions: Mononuclear inflammatory cells of the non-specific immune response are recruited to pancreatic cancer tissues independent of the presence of CP-like changes, may influence the metastatic capacity of the cancer cells, and may contribute to the development of tumours with high angiogenic activity.